(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article discusses the problems that a teacher faces when preparing students, both for writing various types of letters and written statements on given topics. Based on own experience of working with students, the author offers practical recommendations for improving the skills and abilities of writing among students studying the Russian language.